2006
DOI: 10.5194/acpd-6-5357-2006
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensitivity of meteoric smoke distribution to microphysical properties and atmospheric conditions

Abstract: Abstract. Meteoroids entering the Earth's atmopsphere experience strong deceleration and ablate, whereupon the resulting material is believed to re-condense to nanometre-size "smoke particles". These particles are thought to be of great importance for many middle atmosphere phenomena, such as noctilucent clouds, polar mesospheric summer echoes, metal layers, and heterogeneous chemistry. The properties and distribution of meteoric smoke depend on poorly known or highly variable factors such as the amount, compo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(68 citation statements)
references
References 24 publications
4
64
0
Order By: Relevance
“…If the original small Hunten particles are also covered by a condensed ice-layer, this will lower the accretion rate and therefore also require a higher density N H , in order to yield the same embedded density. Recent calculations on the ablation and condensation of meteoric material confirm that densities of N H U comparable to our requirements may well be present (Megner et al, 2006). Considering the capture of the smallest Hunten particles with a radius of just a fraction of a nanometer, they find that densities of N H U (0.2 nm)∼10 11 m −3 may be present.…”
Section: Discussionmentioning
confidence: 84%
“…If the original small Hunten particles are also covered by a condensed ice-layer, this will lower the accretion rate and therefore also require a higher density N H , in order to yield the same embedded density. Recent calculations on the ablation and condensation of meteoric material confirm that densities of N H U comparable to our requirements may well be present (Megner et al, 2006). Considering the capture of the smallest Hunten particles with a radius of just a fraction of a nanometer, they find that densities of N H U (0.2 nm)∼10 11 m −3 may be present.…”
Section: Discussionmentioning
confidence: 84%
“…5 where it is argued that the occurrence of positive particles at the smallest sizes is more consistent with the growth of ice on positively charged condensation nuclei than with either photoelectric charging or the capture of positive ions by neutral aerosol particles. The condensation nuclei being ions rather than meteoric dust is also supported by recent circulation models that show number densities of sufficiently-large meteoric particles that are too low to account for the number densities of charged aerosol particles (Megner et al, 2006(Megner et al, , 2008Bardeen et al, 2008). Section 6 is a short summary and conclusion.…”
Section: Introductionmentioning
confidence: 79%
“…Recent modeling of meteoric smoke production and circulation shows that the smoke particles are carried away from the summer pole by circulation (Megner et al, 2006(Megner et al, , 2008Bardeen et al, 2008). Models for condensation require a minimum particle radius near 0.5 nm for typical conditions (Keesee, 1989;Megner et al, 2008;Gumbel and Megner, 2009;Winkler et al, 2008).…”
Section: Positive Charge On the Smallest Particlesmentioning
confidence: 99%
“…The reason for the comparatively high value of the impact angles found in the experiments, compared to those required for mesospheric dust particles, is most likely that the pure ice particles in the experiments will totally sublimate at lower impact angles (Tomsic, 2001). On the other hand, mesospheric ice particles may contain many small meteoric particles (Rosinski and Snow, 1961;Hunten et al, 1980;Megner et al, 2006) which probably do not sublimate. Havnes and Naesheim (2007) suggested that mesospheric dust particles fragment during impact and that much or all of the ice within which the meteoric smoke particles are embedded, sublimates, while the meteoric smoke particles carry away charge from the surface where the impact takes place.…”
Section: Secondary Charge Production In the Nlc/pmse And Pmse Layermentioning
confidence: 99%
“…The required effectivity for the secondary charge production of the mesospheric dust is much larger than what is observed for pure water-ice particles in experiments. This, combined with a modelling of the impacts on the dust probe grids as a function of payload spin rotation angle, led Havnes and Naesheim (2007) to conclude that a model for the mesospheric dust could be a fairly loosely bound ice particle in which a considerable number of small meteoric particles (Rosinski and Snow, 1961;Hunten et al, 1980;Megner et al, 2006) of radius 1 nm are embedded. Upon impact, the large dust particle was assumed to fragment into many small subparticles each containing one or more meteoric smoke particle.…”
Section: Introductionmentioning
confidence: 99%